Long-Distance Communication between Laryngeal Carcinoma Cells - Ieva Antanavičiūtė; Kristina Rysevaitė; Vykintas Liutkevičius; Alina Marandykina; Lina Rimkutė; Renata Sveikatienė; Virgilijus Uloza; Vytenis Arvydas Skeberdis (2014)
Tunneling nanotubes and epithelial bridges are recently discovered new forms of intercellular communication between remote cells allowing their electrical synchronization, transfer of second messengers and even membrane vesicles and organelles. In the present study, we demonstrate for the first time in primary cell cultures prepared from human laryngeal squamous cell carcinoma (LSCC) samples that these cells communicate with each other over long distances (up to 1 mm) through membranous tunneling tubes (TTs), which can be open-ended or contain functional gap junctions formed of connexin 43. We found two types of TTs, containing F-actin alone or F-actin and α-tubulin. In the LSCC cell culture, we identified 5 modes of TT formation and performed quantitative assessment of their electrical properties and permeability to fluorescent dyes of different molecular weight and charge. We show that TTs, containing F-actin and α-tubulin, transport mitochondria and accommodate small DAPI-positive vesicles suggesting possible transfer of genetic material through TTs. We confirmed this possibility by demonstrating that even TTs, containing gap junctions, were capable of transmitting double-stranded small interfering RNA. To support the idea that the phenomenon of TTs is not only typical of cell cultures, we have examined microsections of samples obtained from human LSCC tissues and identified intercellular structures similar to those found in the primary LSCC cell culture.